THE EFFECT OF NITROGEN FERTILIZER FORM ON THE CONTENT OF SIXTEEN ELEMENTS IN RED CABBAGE - Sylwester Smoleń; Włodzimierz Sady (Acta Scientiarum Polonorum: Hortorum Cultus, 2008)
Various forms of nitrogen fertilizer were applied in the cultivation of red cabbage (in the years 2003–2005), ‘Langendijker’ c.v.: control (unfertilized with nitrogen), Ca(NO3)2, (NH4)2SO4, NH4NO3, CO(NH2)2 applied as solid fertilizers. This experiment aimed at determining the influence of various nitrogen forms on the content of Al, B, Cd, Co, Cr, Cu, Fe, Li, Mn, Mo, Ni, Pb, Sr, Ti, Zn, V in cabbage heads and the changes in the content of the available form of these elements for plants in soil after cabbage cultivation. The heads of plants fertilized with calcium nitrate and urea were characterized by the highest content of Al, Mn, Sr, Zn, Cd and Mo. Urea caused a significant increase in the content of Cu, Li and V, while ammonium nitrate resulted in an elevated level of Fe and Co accumulation in cabbage heads. Fertilization with (NH4)2SO4 led to a substantial decrease in the content of Al, Mo and V, and fertilization with NH4NO3 caused a decline in Sr concentrations in cabbage in comparison with other objects of the experiment. Each nitrogen fertilizer resulted in the decreased concentrations of Ti in cabbage heads. Applied nitrogen fertilizers significantly influenced the contents of readily soluble forms of B, Fe and Pb in soil after cabbage cultivation.